2017
DOI: 10.1177/0267659117746233
|View full text |Cite
|
Sign up to set email alerts
|

A novel augmented venous-drainage model of cardiopulmonary bypass for deep hypothermic circulatory arrest without blood priming

Abstract: The novel augmented venous-drainage CPB and DHCA model in rats could be established successfully without blood priming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…CPB: cardiopulmonary bypass; MHCA: moderate hypothermia circulatory arrest. [Jiang 2017;Liu 2018;Jungwirth 2006], which induces circulatory arrest at 20°C or below. Thus, research on the pathophysiology and testing of new therapeutic methods in MHCA require an MHCA model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CPB: cardiopulmonary bypass; MHCA: moderate hypothermia circulatory arrest. [Jiang 2017;Liu 2018;Jungwirth 2006], which induces circulatory arrest at 20°C or below. Thus, research on the pathophysiology and testing of new therapeutic methods in MHCA require an MHCA model.…”
Section: Discussionmentioning
confidence: 99%
“…Because the blood volume of rats is small, the prime volume of the CPB circuit should be limited. In previous studies, the CPB circuit often only contained an oxygenator and circuits, in which heat exchange was carried out by a homemade cooling blanket and ice bags [Jiang 2017;Fan 2021;Jungwirth 2006]. Although the method for heat exchange did not increase the prime volume, the temperature modulation was inaccurate and inefficient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in order to explore new therapeutic methods in DHCA, there is an urgent need to establish a simple and convenient rodent model for genetic and protein research. Although many rat DHCA models have been reported in the past half century, most of these models were with blood priming, and the postoperative functional and pathological study was no more than 14 days . A rat hypothermic circulatory arrest model was established among different previous temperatures, but few rats survived after the experiments .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, all kinds of animal models for DHCA research have been reported in an endless stream . Rats have been favored by many scholars due to the low price, similar cardiovascular system anatomy with humans and abundant testing methods at the genetic and protein level .…”
Section: Introductionmentioning
confidence: 99%